QUALITY OF SUSTAINABILITY DISCLOSURE AMONG THE ASEAN-5 COUNTRIES AND THE ROLE OF STAKEHOLDERS - Trianaputri, Anisa Ramadhini; Djakman, Chaerul D. (UI Scholars Hub, 2019)
This study was carried out to reveal the actual quality of sustainability disclosure, actuated by some recent studies that pointed out the lack of disclosure quality amid the growing trend of CSR and the tendency that CSR disclosure was dominantly constructed to manage the corporate image. This study also seeks to investigate the role of stakeholder groups (primary, secondary and regulatory stakeholders), by analyzing the sustainability disclosures of 224 primary sector companies among the five emerging markets in Southeast Asia: Indonesia, Malaysia, Singapore, Thailand, and Philippines in the year of 2016. The extensive disclosure index was also employed to assess each disclosure item under the GRI G4 Guidelines. The results revealed that the quality of sustainability disclosure is still low. In this regard, Thailand turns into the country with the highest score, followed by Malaysia and Indonesia. Labor practice aspect becomes the most expressed aspect by the companies, followed by environmental and social aspect. Based on results obtained, it is therefore argued that employees, auditors, mass media, and regulators have roles in encouraging companies to enhance the quality of sustainability disclosure. However, this study does not find a significant influence from the shareholders and international consumers. The contradictory result was found from creditors, conveying that they possess a negative influence on the quality of sustainability disclosure.